Proteínas derivadas da matriz de esmalte e laser de baixa intensidade na regeneração periodontal: revisão de literatura - Jorge, Paula Karine [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The regeneration of the periodontal tissues is dependent on four basic componetes such as appropriate signals, cells, blood supply and scaffold. Each of these elements plays a fundamental role on the healing process in a simultaneous and temporal time frame and is interconnected into the generation of new tissues (TABA et al., 2005). One therapeutic modality available to promote periodontal regeneration is the use of enamel matrix derivative proteins (EMD). These proteins are used with the purpose to mimic specific events that occur in the natural development of the periodontal supporting tissues during odontogenesis (GIANNOBILE et al., 2003; HAMMARSTROM, 1997a; HAMMARSTRÖM et al., 1997b) such as the attachment of cementum to root dentin (TEN CATE, 1996), initiation of cementogenesis (HERITIER, 1982) and induction of the differentiation of the dental follicle cells to cementoblasts (HAMMARSTRÖM, 1997a). There are evidences that enamel proteins have the capacity to promote true periodontal regeneration by inducing the formation of new acellular cementum, periodontal ligament and alveolar bone (KAWASE et al., 2000). Another terapheutic modality proposed to promote tissue regeneration that has been recently evaluated is the use of low level intensity laser irradiation (LLLI). LLLI acts on tissue biomodulation (NICOLAU et al., 2003), inducing intra-cellular metabolic alterations, as well as accelerating cell division, migration and proliferation of fibroblasts (KHADRA, 2005; KHADRA 2005a; KREISLER, 2002). The use of LLLI as well as of EMD have demonstrated potential attributes that may contribute to periodontal regeneration. The purpose of this study is to discuss the use of both terapheutic modalities for periodontal regeneration

A regeneração periodontal está relacionada com alguns elementos básicos como arcabouços, moléculas sinalizadoras, células e suprimento sangüíneo adequados. Cada um desses elementos representa papel fundamental no processo de regeneração, atuando de forma simultânea e em seqüência temporal para a regeneração tecidual (TABA et al., 2005). Uma modalidade terapêutica disponível para promover a regeneração periodontal é a utilização das proteínas derivadas da matriz de esmalte (EMD). Essas proteínas são utilizadas com intuito de mimetizar eventos específicos que ocorrem no desenvolvimento natural dos tecidos de suporte dentários durante a odontogênese (GIANNOBILE et al., 2003; HAMMARSTRÖM, 1997a; HAMMARSTROM et al., 1997b), atuando na inserção do cemento à dentina radicular (TEN CATE, 1996), início da cementogênese (HERITIER, 1982) e indução na diferenciação de células do folículo dental em cementoblastos (HAMMARSTROM, 1997a). Existem evidências de que as proteínas de esmalte têm a capacidade de promover regeneração periodontal verdadeira por induzir a formação de novo cemento acelular, ligamento periodontal e osso alveolar (KAWASE et al., 2000). Outra técnica proposta para a regeneração tecidual que tem sido muito estudada e discutida recentemente é o uso do laser de baixa intensidade (LBI). O LBI atua na biomodulação tecidual (NICOLAU et al., 2003), propiciando alterações metabólicas intra-celulares, além de acelerar a divisão celular, migração e proliferação fibroblástica (KHADRA, 2005; KHADRA 2005a; KREISLER, 2002). Tanto a utilização do LBI como a da EMD têm demonstrado atributos potenciais que podem contribuir na regeneração periodontal. Este trabalho tem por objetivo abordar a utilização da EMD e do LBI na regeneração periodontal
Keywords: Esmalte dentário; Lasers; Regeneração tecidual guiada; Dental enamel